Pengaruh Model Pembelajaran Problem Based Learning Pada Materi Sistem Koloid Terhadap Hasil Belajar Kimia Siswa Kelas XI MIA di SMA Negeri 1 Lirung - Yeni Gerice Awawangi; I Dewe Ketut Anom; Meyti Jeanne Rampe (Oxygenius Journal Of Chemistry Education, 2021)
Problem based lerning is a learning model that involves students to solve a problem through the stages of the scientific method so that students can learn knowledge related to the problem and at the same time have the skills to solve the problem. This research aims to determine the effect of the Problem based lerning learning model. on student learning outcomes. The research was conducted at SMA Negeri 1 Lirung in the 2018/2019 academic year. The population was all classes in SMA Negeri 1 Lirung with a sample of class XI MIA 2 and class XI MIA 3 as an experimental class of 20 students. With the research design Posttest Only Control Design with the True Experimental method. The results of the calculation of the test (t) the mean similarity of the two parties obtained tcount (4.406) and ttable 2.002 at the level of α = 5%. This shows that the value of t is greater than t table, so the hypothesis Ho is rejected and Ha is accepted, so it can be concluded that there is a significant influence on the problem-based lerning learning model on student learning outcomes of Chemistry at SMA Negeri 1 Lirung.